Towards a Data-Driven Estimation of Resilience in Networked Dynamical Systems: Designing a Versatile Testbed - Fischer, Tobias; Rings, Thorsten; Rahimi Tabar, M. Reza; Lehnertz, Klaus (Frontiers in Network Physiology, 2022)
Estimating resilience of adaptive, networked dynamical systems remains a challenge. Resilience refers to a system’s capacity to absorb exogenous and/or endogenous disturbances and to reorganize while undergoing change so as to still retain essentially the same functioning, structure, and feedbacks. The majority of approaches to estimate resilience requires exact knowledge of the underlying equations of motion; the few data-driven approaches so far either lack appropriate strategies to verify their suitability or remain subject of considerable debate. We develop a testbed that allows one to modify resilience of a multistable networked dynamical system in a controlled manner. The testbed also enables generation of multivariate time series of system observables to evaluate the suitability of data-driven estimators of resilience. We report first findings for such an estimator.